English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-12-03 10:02:41 · 13 answers · asked by pvamu19 1 in Science & Mathematics Mathematics

13 answers

3x-4=2x+8-5x
3x-4=-3x+8
6x=12
x=2

2006-12-04 16:14:40 · answer #1 · answered by arpita 5 · 0 0

2

2006-12-03 16:42:50 · answer #2 · answered by Mehbooba 4 · 0 0

2x + 4 = x + 8 combine like words. The x's and the constants. first subtract 4 from each area and we get 2x = x + 4 now subtact x from each area and we get x = 4 the answer 5x - 2 = 3x - 8 lower back combine like words with the aid of including 2 to each area and we get 5x = 3x - 6 subtract 3x from each area 2x = -6 divide with the aid of two each area of the equation and we get x = - 3 3x - 8 = 2 - 2x combine words 3x = 10 - 2x upload 2x t each area 5x = 10 divide each area with the aid of 5 and we get x = 2 x/5 = 10 multiply each area with the aid of 5 and we get x = 50 x/5 < 16 mulltiply each area with the aid of 5 and we get x < 80

2016-11-23 15:02:37 · answer #3 · answered by ? 4 · 0 0

3x-2x+5x=+8+4
+6x=+12
+x=+2

2006-12-04 02:03:46 · answer #4 · answered by mani k 2 · 0 0

3x - 4 = 2x + 8 - 5x
3x - 4 = 8 - 3x
3x + 3x = 8 + 4
6x = 12
x = 12/6
x = 2

2006-12-04 22:57:31 · answer #5 · answered by Anonymous · 0 0

3x-4=2x+8-5x add 3x to each side
6x-4=8 add 4 to each side
6x=12 divide by 6
x=2

2006-12-03 10:06:22 · answer #6 · answered by yupchagee 7 · 0 0

3x-4=2x+8-5x
3x-4=-3x+8
3x+3x=8+4
6x=12
x=12/6
x=2

so the value of x=2

2006-12-04 04:08:36 · answer #7 · answered by Hemali 2 · 0 0

3x - 2x + 5x = 8 + 4
6x = 12
x = 2

2006-12-03 18:58:22 · answer #8 · answered by mad_integer 3 · 0 0

First combine all like terms:

3x - 4 = -3x + 8

Now separate the x by subtraction and addition:

6x = 12
x = 2

2006-12-03 10:05:29 · answer #9 · answered by Anonymous · 0 0

First of all, group symilar items on each size, that means:
3x-4=-3x+8
Now put all items containing an x on one side (usually but not neccesarily, left), all others on the other side (when you take something from one side of the equation to the other, its sign changes):
3x+3x=8+4
So now you have
6x=12
Now you divide by the coefficient of x, which is 6:
x=2

So this is your answer: x=2

Good luck!

2006-12-03 10:08:33 · answer #10 · answered by OR13 2 · 0 0

fedest.com, questions and answers